PREPARATION AND CHARACTERIZATION OF HETEROGENEOUS MONOVALENT PERMSELECTIVE IONEXCHANGE MEMBRANE WITH SURFACE MODIFICATION - Faikar Ihsan, Muhammad
As technology advances, the demand for membrane-based purification processes is rapidly increasing. One such application is the selective separation of monovalent ions from mixed ionic solutions. Ion exchange membranes (IEMs) offer a promising solution to this industrial need. However, the development of IEMs with optimal performance requires careful consideration of their physical, electrochemical, and mechanical properties. High permselectivity, low electrical resistance, and excellent mechanical and chemical stability are all highly desirable characteristics for IEMs. Unfortunately, achieving the best in one property often leads to compromises in others. This research investigates the modification of a commercial IEM using a polydopamine (PDA) coating to create a heterogeneous ionic membrane with high permselectivity while maintaining other desirable properties. The influence of various process parameters, including temperature, aeration, and hydrogen peroxide pretreatment, on IEM characteristics was systematically investigated. Based on the statistical investigation using a Box-Behnken design, the response surface analysis and ridge analysis found the optimum point for the anion membrane at a solution temperature of 43.13°C, aeration time of 63 minutes, and 0.8% hydrogen peroxide concentration for pretreatment. For the cation membrane, the optimum point was found to be a solution temperature of 57.3°C, aeration time of 60 minutes, and 2.3% hydrogen peroxide concentration for pretreatment. The optimization for the anion membrane is predicted to result in a membrane with a predicted monovalent ion permselectivity value of 1.5 times that of the bivalent ions. The optimization also resulted in stable IEC, WU, and WCA values. For the cation membrane, the optimization is predicted to result in a monovalent ion permselectivity value of 8.3 times that of the bivalent ions. This optimization can result in good IEC, WU, and WCA capabilities.